Integrating Feminist Perspectives with the Religious Studies Curriculum: Setting the Question - Carmody, Denise Lardner (Horizons, 1989)
My assignment is to set the question for our teaching workshop on integrating feminist perspectives into the religious studies curriculum. In reflecting on this assignment in light of the full program sketched in the brochure for the workshop, I found three journalistic questions coming to mind. The six specialized sub-workshops seemed to deal quite comprehensively with the question of how to effect the integration of feminist perspectives into the religious studies curriculum. Mary Jo Weaver's plenary address promised to treat from the perspective of American religious history where American women now are and may hope to arrive tomorrow. That left the matter of why we should be assembled here this evening, and though I'm sure that many of the other presenters will address it substantially, I have taken it as the proper focus for this kick-off presentation. Inevitably, speaking about why it is important to represent women's voices will imply how we may best accomplish this, but let us begin by reminding ourselves of the telos of our workshop—the prospective good that brings us together. My ruminations on this topic will have three sub-topics; students' needs, intellectual justice, and fidelity to God.This past semester I taught two typical courses: "Women and World Religions" and "The New Testament and Literature." Both courses are part of the Tulsa Curriculum, our general education sequence. Each course had about thirty students, but only two of those in "Women and World Religion" were men, while "The New Testament and Literature" had about fifteen men. It is hard to say, though, which sex was more in need of feminist perspectives.